Novel Compound Heterozygous Mutations in TTI2 Cause Syndromic Intellectual Disability in a Chinese Family - Wang, Rongrong; Han, Shirui; Liu, Hongyan; Khan, Amjad; Xiaerbati, Habulieti; Yu, Xue; Huang, Jia; Zhang, Xue (Frontiers in Genetics, 2019)
Telomere maintenance 2 (TELO2)-interacting protein 2 (TTI2) interacts with TTI1 and TELO2 to form the Triple T complex, which is required for various cellular processes, including the double-strand DNA break response, nonsense-mediated mRNA decay, and telomerase assembly. Herein, we identified compound heterozygous mutations in TTI2 using whole-exome sequencing in a Chinese family with a recessive inheritance pattern of syndromic intellectual disability. The patients displayed intellectual disability, aggressive and self-injurious behaviors, facial dysmorphic features, microcephaly, and skeletal anomalies. In addition, one patient showed cerebral white matter abnormality. Maternal novel indel mutation resulted in a premature termination codon and nonsense-mediate mRNA decay. Paternal reported c.1100C>T mutation changed the highly conserved proline to leucine that located in the DUF2454 domain. Immunoblotting experiments showed significantly decreased TTI2, TTI1, and TELO2 in the patients’ lymphocytes. These results indicated that TTI2 loss-of-function mutations might cause an autosomal-recessive syndromic intellectual disability by affecting the Triple T complex. Our report expands the genetic causes of syndromic intellectual disability in the Chinese population.